Vocational Training Regulations and the Process Behind Them - Kuppe, Anna Maria [Herausgeber]; Lorig, Barbara [Herausgeber]; Stöhr, Andreas [Herausgeber] (Bundesinstitut für Berufsbildung, 2011)
"This brochure informs readers about Germany's unique process for developing initial vocational training regulations. These regulations are the basis for initial vocational education and training within the dual system (a company-based apprenticeship combined with part-time vocational school) in which many young people in Germany gain their first vocational qualifications. The great advantage of this process is that its outcomes are fully accepted by all parties involved in initial vocational training practice, since the parties concerned – employers’ organisations on behalf of the companies and trade unions on behalf of employees – are fully involved in all important decisions about the content, objectives, duration, and requirements of initial vocational training. How does this process work? Experts from initial vocational training practice work jointly with the Federal Institute for Vocational Education and Training (BIBB) on the drafting of new training regulations, and they confer with experts from the part-time vocational schools in order to coordinate these regulations with the draft framework curricula. Employers and trade unions then publicise the new training regulations in their firms, and the federal government enacts them in law." (BIBB)
Dt. Ausgabe u.d.T.: Ausbildungsordnungen und wie sie entstehen ...
Spätere Ausgaben u.d.T.: Training regulations and how they come about
Keywords: S 2.2 Ordnungen & Ordnungsverfahren; S 2.2.1 Ordnung von Ausbildungsberufen; S 3.5.2.2 Bundesinstitut für Berufsbildung (BIBB); Neuordnung der Ausbildungsberufe; Ausbildungsordnung; Verfahren